Estilos de ensino na educação física escolar: tradução e adaptação transcultural do instrumento de auto avaliação por professores de Educação física - Oliveira, Vitor Pereira de (2023)
Teaching Styles Spectrum, introduced by Muska Mosston, provides the teacher with different ways to conduct the class, stimulating various domains of human development. It is extremely helpful that teachers have training in teaching styles so that they can incorporate them into their teaching practice. One of the ways of knowing the styles that teachers have been using is through self-assessment. The Spectrum Inventory Instrument has been used in several countries, mainly to identify teaching styles that have been used in school environments and sports training. Therefore, the present study aims at the translation and cross-cultural adaptation of the self-assessment instrument of teaching styles adopted in Physical Education classes at school. The methodological process covered six stages. The first stage was the translation of the instrument from English to Portuguese, carried out by two Brazilian translators, bilingual, independent and proficient in the English language. The second step was the synthesis of the translated versions into a single version, which compared the different translations and assessed their discrepancies. The third stage consisted of the evaluation of the synthesis by experts. Three professors were selected, who, within their specialty, carried out an evaluation considering linguistic elements, teaching styles and school physical education. The fourth verified the understanding of the target audience, based on the evaluation by six Physical Education teachers, who work in Basic Education. At this stage, they were asked to complete the instrument and indicate any doubts, misunderstandings, disagreements, or constraints that could arise. The fifth step comprised the reverse translation of the Portuguese language version back to the source language, in order to verify whether the translated version reflects the content as in the original version. Finally, the last stage consisted of carrying out a pilot study, where the self-assessment of teaching styles instrument, in the Portuguese language version, was applied to a small group of school physical education teachers, technically representative of the target population. The product of this research was the instrument itself, which was translated and cross-culturally adapted. With this, we can qualify the teacher's work to the extent that Physical Education teachers perform self-assessment in order to improve their pedagogical practice. Finally, we contribute to the scientific development of the area by providing an instrument for researchers who seek to investigate teaching styles.